TheReligious Discourse: A Study of the Origins of Difference and the Foundations of Understanding and Coalition - refice, Belkheir (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
This article aims to search for the first origins of the difference in the interpretation of religious discourse, and the resulting formation of many different and even rival sects. This is done by answering the following questions: To what extent is it possible to talk about renewing and unifying religious discourse in light of the multiplicity of sects and different trends? Is this possible in light of the existence of those who claim to be the surviving sect? What are the means and mechanisms that can be relied upon to achieve this? How can we address the issues of fanaticism and takfir to replace them with understanding and reflection